Lighthouse: Dwelling on a Remote Island. A Bachelor Diploma Project within a Narrative Framework - Proosten, Mark; Recker, Katrin (Writingplace, 2018)
Within this article, a curious storyteller will guide our way to remotely situated islands and their marvellous stories and stubborn inhabitants, invented by students. In the summer of 2016, the bachelor diploma students of the department of Wohnbau at the RWTH-Aachen University were asked to develop a dwelling for a lighthouse keeper, a house with a beacon. Within this article, we aim to give an insight into the project’s boundaries, by describing the project brief and our tutoring approach. With this article and the introduction of our own curious narrator, we intend to show how our approach has resulted in a great variety of narrated tales that were combined with profound building techniques and methods. The literary framework of the assignment, departing from a place that could not be visited and from a particular character, made the student's observations and readings of both programme and context extremely focused. The students explored their islands and treated the challenges for their protagonist to dwell on them in an accurate manner. They became sensitive to basic conditions of dwelling, such as landscape, climate, materials, building methods, and applied these conditions in their distinctive and tangible design solutions. In addition, the game rules of the entire project, in combination with the detailed requirements for the final presentation, helped to examine the skills and knowledge we deem indispensable to obtaining the bachelor’s degree. The students gained the understanding necessary to handle a relatively small architectural design project from concept to detail through imagining their own narrative framework and making their unique design of a lighthouse the starring role of their very peculiar and fantastic story.